Okazje jako przedmiot badań w zakresie zarządzania strategicznego - Krupski, Rafał (Business Opportunities as a Research Subject in Strategy Management, 2008)
The article presents a new paradigm's basis - the identification of an organization strategy in a turbulent environment. The structure of a mentioned strategy concerns resources, business opportunities and their filter, identification and application. The link of these elements is an organization's mission - the only one element derived from classic conceptions. Moreover, the article presents the results of research confirming the great role of a new strategy's formulating.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 156-162